The Influence of Students’ Personality on Their Speaking Ability in English - Hardian Alvin Eftiama; Titi Rokhayati; Ismawati Ike Nugraeni (Scripta : English Department Journal, 2022)
The objectives of this study are to reveal student’s personality, the students’ speaking ability, dan to find out if there is any specific influence of student’s personality (extrovert introvert) on their speaking ability in English Education Program of Universitas Muhammadiyah Purworejo. This research was quantitative research. The instruments of this research were questionnaire and documentation. Data collection techniques used questionnaire and documentation. Data analysis used descriptive analysis and inferential analysis. This study shows that (1) the dominant students’ personality was in extrovert category with the means score = 84.47. (2) The students' speaking ability was in good category with the means score = 77.55 at the interval of 70 - 79. (3) There was positive and significant influence of students’ personality on speaking ability with the value of regression analysis was 0.486 and the significant level score 0.000 was lower than 0.05. The regression model (students’ personality) was able to be explained its influence on speaking ability by 22.22%, while the influence of 77.78% is explained by other factors that are not used in this regression model.